Adverse impact of sexual dysfunction in chronic prostatitis/chronic pelvic pain syndrome. - Lee, S; Liong, M; Yuen, K; Leong, W; Cheah, P; Khan, N; Krieger, J (2008)
OBJECTIVES: To examine the prevalence, characteristics, and impact of sexual dysfunction in our primary care referral population. METHODS: Participants seeking treatment for chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) were recruited from general urology clinics. The subjects completed the National Institutes of Health-Chronic Prostatitis Symptom Index, International Index of Erectile Function-5, and selected questions from the University of Washington Symptom Score. Additional information on demographics and medical and treatment history were also obtained. Sexual dysfunction was defined as self-reported erectile dysfunction (ED) or ejaculatory difficulty, or both. RESULTS: Of 296 participants with CP/CPPS, 214 (72.3%) reported sexual dysfunction. The National Institutes of Health-Chronic Prostatitis Symptom Index total score averaged 22.5 +/- 6.9 for participants with sexual dysfunction compared with 20.4 +/- 7.8 for participants who did not report sexual dysfunction (P = 0.03). Of the 214 participants with sexual dysfunction, 54 (25.0%) complained of ED only, 71 (33.4%) complained of ejaculatory difficulties only, and 89 (41.6%) complained of both ED and ejaculatory difficulties. Men reporting both ED and ejaculatory difficulty reported worse CP/CPPS symptoms (analysis of variance, P = 0.042) and worse quality of life (analysis of variance, P = 0.006) than men without sexual dysfunction. CONCLUSIONS: Sexual dysfunction was reported by almost three quarters of patients with CP/CPPS. Patients with CP/CPPS and sexual dysfunction experienced substantially worse symptoms, particularly worse quality of life, than other patients with CP/CPPS. Sexual dysfunction merits consideration as an important aspect of CP/CPPS and a potential outcome measure.